PENERAPAN KARAKTER NASIONALIS DAN MANDIRI DALAM BUDAYA SEKOLAH DASAR - Aghna Mau’ila Darmatiana; Fadhila Azzahra; Firda Khoirina; Muhammad Hasbi Hidayatullah; Viki Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore the implementation of nationalist and independent characters in school culture. Nationalist and independent characters are two important aspects in developing students who are responsible, have integrity and are ready to face global challenges. This research used a qualitative method which is depcriptive. The results show that the implementation of nationalist character is reflected through activities such as flag ceremonies, commemoration of national days, and integration of national values in the curriculum. Meanwhile, independent character is developed through programs that encourage students to take initiative, think critically and manage time effectively, such as independent projects and extracurricular activities that demand individual responsibility. These two characters, when applied consistently and integrated into the school culture, have been proven to form students who are not only academically smart, but also have a strong personality and love for the country. This implementation requires cooperation from all school parties, including teachers, principals and parents, to create an environment conducive to character development. This research makes an important contribution to the development of character education theory and implementation practices in schools. The findings are expected to serve as a reference for policy makers and education practitioners in developing more effective programs to shape students' character.